2012
DOI: 10.1136/jnnp-2012-303791
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the serotonin transporter gene and post-stroke depression: a meta-analysis

Abstract: The 5-HTTLPR SS genotype may be a risk factor for PSD. The 5-HTTLPR LL genotype showed a significant negative association with PSD. Further research to assess the sensitivity and specificity of predicting the risk of developing PSD by screening for the 5-HTTLPR genotype in stroke patients is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 41 publications
1
42
1
Order By: Relevance
“…Also, subjects in that study were not stratified by pre-morbid mood disorders; Our study only showed genetic associations with PTD when pre-morbid subjects were excluded or whose effects were adjusted for in multivariate analysis (Table III). Similarly, studies in post-stroke depression suggest S-homozygotes show increased rates of depression, but many of these studies did not exclude or separately analyse subjects with a history of pre-injury depression [34].…”
Section: Discussionmentioning
confidence: 98%
“…Also, subjects in that study were not stratified by pre-morbid mood disorders; Our study only showed genetic associations with PTD when pre-morbid subjects were excluded or whose effects were adjusted for in multivariate analysis (Table III). Similarly, studies in post-stroke depression suggest S-homozygotes show increased rates of depression, but many of these studies did not exclude or separately analyse subjects with a history of pre-injury depression [34].…”
Section: Discussionmentioning
confidence: 98%
“…The short variation (S) allele of the 5-HTTLPR polymorphism led to 14 repeats of base pair sequences. In contrast, a long variation (L) allele led to 16 repeats of base pair sequences (Mak et al, 2013). The LL genotype had a band of 419 bp; the LS genotype had bands of 419 and 376 bp; and the SS genotype had a band of 376 bp.…”
Section: Resultsmentioning
confidence: 99%
“…PSD leads to a diminished quality of life, delayed recovery of neurological function, increased mortality, and a greater burden on families and society (Hackett et al, 2010). In recent years, much attention has been paid to the serotonin (5-hydroxytryptamine; 5-HT) transporter gene-linked polymorphic region (5-HTTLPR) genotype in PSD patients and the neurotransmitter serotonin hypothesis, but current studies show that the correlation between 5-HTTLPR and PSD is controversial (Fang and Cheng, 2009;Choi-Kwon et al, 2012;Mak et al, 2013). The present study further explores the association between the 5-HTTLPR and PSD from a biological viewpoint in order to provide a theoretical basis for the etiology of PSD.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that SERT polymorphisms are not related to the presence of poststroke depression or responsiveness of SSRIs on depression. Although the 5-HTTLPR s/s genotype has been suggested as a risk factor for poststroke depression,40 heterogeneous study designs preclude a conclusion. Further studies are needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%